2023
DOI: 10.1093/jsxmed/qdad009
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized sexual dysfunction in gay and bisexual men after prostate cancer treatment: the antecedents and impact of anodyspareunia

Abstract: Background Anodyspareunia may be an adverse outcome of prostate cancer (PCa) treatment for gay, bisexual, and other men who have sex with men (GBM). Aim The aims of this study were to (1) describe the clinical symptoms of painful receptive anal intercourse (RAI) in GBM following PCa treatment, (2) estimate the prevalence of anodyspareunia, and (3) identify clinical and psychosocial correlates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Given the small number of non-White and Hispanic participants, racial and ethnic categories were collapsed into either non-White and/or Hispanic (i.e., men of color) or White, non-Hispanic. This method of combining small numbers of non-White and Hispanic participants into one group is similar to other studies (Ross et al, 2023;Umaretiya et al, 2021;Wheldon et al, 2023). Continuous age was collapsed into either 65 and younger or older than 65, which was the median age of our sample and is consistent with the Restore-1 study (Rosser et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Given the small number of non-White and Hispanic participants, racial and ethnic categories were collapsed into either non-White and/or Hispanic (i.e., men of color) or White, non-Hispanic. This method of combining small numbers of non-White and Hispanic participants into one group is similar to other studies (Ross et al, 2023;Umaretiya et al, 2021;Wheldon et al, 2023). Continuous age was collapsed into either 65 and younger or older than 65, which was the median age of our sample and is consistent with the Restore-1 study (Rosser et al, 2020).…”
Section: Discussionmentioning
confidence: 90%
“…These measures are based on heteronormative assumptions regarding sex, despite growing evidence that gay and bisexual men find resuming anal sexual activity following cancer treatment challenging, in part, because of anodyspareunia. 5,6…”
Section: Patient Reported Outcome Measuresmentioning
confidence: 99%
“…In the largest study to date of gay and bisexual men treated for prostate cancer, 1 in 7 reported severe, persistent, and distressing anodyspareunia. 5 However, despite the estimated prevalence of anodyspareunia in gay and bisexual men undergoing treatment, the concern is largely ignored in clinical consultations. When surveyed about topics discussed with cancer care clinicians before receiving treatment, only 6% of gay and bisexual men reported discussing the potential for increased pain, and 8% discussed the potential loss of pleasure during receptive anal intercourse.…”
Section: Patient Counselingmentioning
confidence: 99%
See 2 more Smart Citations